The quicksand question - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 2002)
When someone steals the money the town has been collecting to help the ducks, Josh and his friends try to find the thief.
"A Stepping Stone book."
Grades: 2-4.
Keywords: Robbers and outlaws -- Fiction; Ducks -- Fiction; Mystery and detective stories